Chlorhexidine in operative dentistry - A review - Tanvi Sanjay Satpute; Sanjyot A Mulay (Wolters Kluwer Medknow Publications, 2021)
This review aims to explore existing literature and provide information about techniques that have been employed to incorporate chlorhexidine (CHX) in dental materials, its antimicrobial effectiveness, and its effects on the pulp and dental restorations, in addition to its possible side effects. For both dentists and patients, one of the most important aspects of dental restorations is its longevity. Thus, the objective should be elimination of bacteria and bacterial remnants that can be responsible for recurrent caries, postoperative sensitivity, and ultimately failure of the restoration. Searches were carried out on various online databases including PubMed. Keywords were chosen to assess the properties of various dental materials containing CHX. Methods of introducing CHX in restorative materials were also searched. Studies were selected based on relevance, with a preference given to recent research. A range of antibacterial agents have been incorporated into experimental as well as commercial dental restorative materials to provide antibacterial activity. CHX has demonstrated to be effective and safe against bacterial plaque and biofilms. In addition to its plaque-inhibiting effect, CHX displays other properties beneficial for use in Operative Dentistry.